Utilization of Local Feedstuffs for Native Chickens - A P Sinurat (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 1999)
Local feed-stuffs can be used to formulate diet for native chickens. The utilization of a feed ingredient should consider some factors such as the quantity available, nutrient compositions, price and limiting factors such as anti-nutrient or toxins that exist in the feed ingredient. Some potential local feed ingredients that can be used for native chickens are rice bran, cassava and its  by-product,  coconut  meal,  soybean  curd waste,  palm  oil  by-products,  shrimp  head  and  snail.  Research  results  on  the utilization of these ingredients in poultry feed are discussed in this paper. The application of the research results to make feed for native chickens required knowledge on diet formulation that includes the nutrient requirement for the chickens, calculation methods and techniques for mixing feed.   Key words: Native chickens, local feedstuffs, nutrient composition, nutrient requirement